Influence of weight loss on myocardial performance index - Dayi, Sennur Unal; Kasikcioglu, Hulya; Uslu, Nevzat; Tartan, Zeynep; Uyarel, Huseyin; Terzi, Sait; Hobikoglu, Gultekin; Okmen, Ertan; Cam, Nese (Heart and vessels, 2006)
Obese patients may have a phase of asymptomatic left ventricular dysfunction. A combined myocardial performance index (MPI) has been demonstrated to be a useful index to estimate left ventricular function and to predict the prognosis of patients with heart failure. The objective of the study was to determine the influence of weight loss on MPI. A total of 18 obese patients (3 men, 15 women, mean age 49.6 +/- 5.5 years, body mass index [BMI] >30 kg/m(2)) were investigated in the study. All patients were treated with a multidisciplinary approach consisting of a hypocaloric diet and orlistat therapy (120 mg three times daily), and all of them underwent two-dimensional and Doppler echocardiographic examination two times before starting the study and after a period of weight loss. Using echo-Doppler methods, ejection fraction, peak velocities of early (E) and late (A) diastolic filling, the E/A ratio, deceleration time (DT), isovolumic contraction time (IVCT), isovolumic relaxation time, ejection time, and MPI were measured. The MPI was obtained by subtraction ejection time from the interval between cessation and onset of the mitral flow. All patients lost at least 10% of their initial body weight, with a mean decrease of 10.8 +/- 3.7 kg. This was associated with significant reductions in BMI with a mean decrease 4.5 +/- 1.4 kg/m(2). Compared with baseline, after weight loss the E/A ratio of 1.01 +/- 0.22 before treatment increased to 1.17 +/- 0.26 (P = 0.012), left ventricular mass index decreased from 88 +/- 23 to 82 +/- 19 g/m(2) (P = 0.028), IVCT from 71 +/- 20 to 53 +/- 30 ms (P = 0.004), DT from 233.65 +/- 38.14 to 196.72 +/- 47.73 s (P = 0.004), and MPI from 0.63 +/- 0.13 to 0.50 +/- 0.13 (P = 0.0001). Weight loss ameliorates MPI and seems to be a clinically relevant measurement of left ventricular global function, and may prove to be a valuable tool in assessing the risk of developing heart failure.